2004
DOI: 10.1590/s1516-14392004000100021
|View full text |Cite
|
Sign up to set email alerts
|

Stress and integrity analysis of steam superheater tubes of a high pressure boiler

Abstract: Sources that can lead to deterioration of steam superheater tubes of a high pressure boiler were studied by a stress analysis, focused on internal pressure and temperature experienced by the material at real operating conditions. Loss of flame control, internal deposits and unexpected peak charge are factors that generate loads above the design limit of tube materials, which can be subjected to strain, buckling, cracks and finally rupture in service. To evaluate integrity and dependability of these components,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…It can be considerably different at various positions on the tube in longitudinal and circumferential direction, and it may increase gradually over several years as a consequence of oxide scale thickening. [10,11] Often, the steel temperature during service exposure is estimated only afterward based on the measured thickness of grown oxide scales, but apart from the uncertain assumptions on the kinetics of scale formation, this cannot account for already occurred spallation. Calculations of the temperature at the steel surface based on measurements of the steam temperature at the inlet and outlet of the loops are also difficult because additional information on the pressure, heat flux, and flow rate of the steam, as well as the influence of already formed oxide phases, needs to be considered [11,12] ; the corresponding phases, however, are often unknown.…”
Section: A Exposure Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be considerably different at various positions on the tube in longitudinal and circumferential direction, and it may increase gradually over several years as a consequence of oxide scale thickening. [10,11] Often, the steel temperature during service exposure is estimated only afterward based on the measured thickness of grown oxide scales, but apart from the uncertain assumptions on the kinetics of scale formation, this cannot account for already occurred spallation. Calculations of the temperature at the steel surface based on measurements of the steam temperature at the inlet and outlet of the loops are also difficult because additional information on the pressure, heat flux, and flow rate of the steam, as well as the influence of already formed oxide phases, needs to be considered [11,12] ; the corresponding phases, however, are often unknown.…”
Section: A Exposure Conditionsmentioning
confidence: 99%
“…[10,11] Often, the steel temperature during service exposure is estimated only afterward based on the measured thickness of grown oxide scales, but apart from the uncertain assumptions on the kinetics of scale formation, this cannot account for already occurred spallation. Calculations of the temperature at the steel surface based on measurements of the steam temperature at the inlet and outlet of the loops are also difficult because additional information on the pressure, heat flux, and flow rate of the steam, as well as the influence of already formed oxide phases, needs to be considered [11,12] ; the corresponding phases, however, are often unknown. Enormous temperature gradients were calculated for plant exposed tubes [1,13] as a consequence of huge temperature differences between the combustion gas and the steam.…”
Section: A Exposure Conditionsmentioning
confidence: 99%
“…Intergranular failure is caused by the coalescence of cavities along the grain boundaries and characterizes the beginning of tertiary creep. [14] The proposed model and experimental results as well as previous studies [15] have identified cavities at grain boundaries to appear more frequently and grow more quickly than those elsewhere in the microstructure, therefore playing a critical role in material creep life.…”
Section: Introductionmentioning
confidence: 65%
“…Equation [13] is adapted as follows to generate Eq. [14] for the growth rate of the radius _ r: r now represents the hydrostatic stress instead of the chemical driving force (analogous to our modifications to CNT), the diffusion coefficient D 0 is replaced with that for vacancy diffusion D v , the mean site fraction u 0 is replaced by the vacancy concentration N V and the sintering stress term (2c/r) now incorporates the free surface energy c m . X is redefined from the molar volume to the atomic volume and correspondingly the Boltzmann constant k b is used in place of the gas constant R.…”
Section: Heterogeneous Nucleationmentioning
confidence: 99%
“…xtOkt "1 [1613] "Ov=xDN=OQB |@=QN |UQQ@ x@ w OvOQm hw]at XNWt |Q=OQ@xQy@ |v=tR V}=tR; w |Qwv AwmUwQm}t '|O=a@= |Q}oxR=Ov= R= u=tRsy |xO=iDU= =@ R}v [17] [1] "OvDUy =yQD}yQB wU ' [2] "OvDUy '|WRN CUmW w C}yQw= wv QO QD}yQB wU Q=Wi w =tO [3] &CU=yQD}yQBwU x@ jraDt Qr} w@ QO |@=QN u} QDW}@ =y|@=QN u}= QDW}@ Cra 'xOW s=Hv= |=y|UQQ@ QO [4] "CU= QFwt Q=}U@ u; |@=QN |iQat |oDUN VRN w VRN '|oDUN 'COtx=Dwm w COtOvr@ V}=tQoV}@ |@=QN Cra |UQQ@ |= Q@ |i=Qowr=Dt VwQ R= 'OOaDt |=yVQ= Ro QO [5] "CU= xOW R= =yVywSB R= |[a@ QO u}vJty [7w6] "CU= xOW xO=iDU= QD}yQB wU |=yxrwr Ct=N[ uOW lR=v |Q}oxR=Ov= [8] [9]…”
mentioning
confidence: 99%